A Comparative Analysis of the Tasks from the Selected Mathematics Textbooks of Singapore and Indonesia - Varetha Lisarani; I Nengah Parta; Tjang Daniel Chandra (Jurnal Pendidikan Sains, 2018)
Abstract: This is a content analysis study that aims to analyze the tasks in Pythagorean Theorem unit contained in Indonesian mathematics textbooks and compare them to those of Singapore using the framework to analyze tasks in the textbook with three dimensions of analysis: representation form, contextual feature, and degree of openness. The result of the study shows that in Singaporean Mathematics textbook, verbal representation tasks and closed-ended tasks are commonly found throughout the textbook, meanwhile, application and non-application tasks are divided into exactly a half. In Indonesian Mathematics textbook, combination tasks, non-application tasks, and open-middled tasks are the most common tasks found.Key Words: task, mathematics textbook, pythagorean theoremAbstrak: Penelitian ini merupakan analisis konten yang bertujuan untuk menganalisis tugas yang termuat dalam buku teks matematika Indonesia untuk kemudian dibandingkan dengan tugas-tugas pada buku teks matematika Singapura menggunakan kerangka kerja untuk menganalisis tugas pada buku teks yang memuat tiga dimensi analisis yaitu bentuk representasi, fitur kontekstual, dan derajat keterbukaan. Hasil penelitian menunjukkan bahwa pada buku teks matematika Singapura, tugas dengan representasi verbal dan tugas tertutup adalah jenis yang paling banyak muncul, sedangkan tugas aplikasi dan non-aplikasi terbagi tepat menjadi dua. Pada buku teks matematika Indonesia, tugas dengan kombinasi representasi, tugas non-aplikasi, dan tugas open-middled adalah jenis yang paling sering muncul.Kata kunci: tugas, buku teks matematika, teori pitagoras